APEX and NEM find common ground - Abd Razak, Dzulkifli (2010)
THE New Economic Model (NEM) is shaping up to be a booster for the Higher Education Ministry's Accelerated Programme for Excellence (APEX) agenda in particular, and higher education in general, through its Strategic Plan. Realising that the higher education sector needs help, the NEM report enumerates a number of policy suggestions that must now be put into practice to bolster the implementation of the Model. These pertain to the areas of human resource and talent management that are said to be lagging behind in what it takes to move Malaysia forward economically.